Vishnu with six arms -020 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Here Vishnu can be seen with the standard artefacts in four hands - Shankha, Chakra, Gada, and Padma. The 5th arm holds a bow. The 6th one, bottom right-side is an unidentified object.